O21.3 Pre-therapy inflammation/coagulation activation and long-term cd4 response to antiretroviral therapy. (13th September 2015) - Achhra, AC; Phillips, AN; Emery, S; MacArthur, RD; Furrer, H; De Wit, S; Losso, MH; Law, MG
Abstract : Background: Pre-antiretroviral therapy (ART) inflammation/coagulation activation biomarkers predict clinical outcomes, but whether they predict CD4 response to ART initiation is unknown. Methods: Study cohort was a subset of 2 international trials, SMART (evaluating continuous versus interrupted ART) and FIRST (evaluating 3 first-line ART regimens with ≥2 classes). At the start of follow-up (baseline), participants had to be ART-naïve/off ART, have C-reactive protein (CRP), interleukin-6 (IL-6) and D-dimer measured and be (re)initiating ART. Using random effects linear models, we assessed the association between quartiles of each of the baseline biomarker and change in CD4 to up to 24 months after ART-initiation. Analyses adjusted for baseline CD4, study arm, follow-up time and other known confounders. Sensitivity analyses included separate analyses by trials and excluding the interrupted ART arm in SMART. Results: Overall, 1084 individuals (659 from SMART (26% ART naïve) and 425 from FIRST) met the eligibility criteria, providing 8264 CD4 measurements. 75% were male with the mean age of 42 years, 37% and 47% were white and black respectively, and 10% and 33%, respectively, were hepatitis B and C positive. The median (inter-quartile range) baseline CD4 (cells/mm 3 ) were 360 (265–473) overall and 416 (350–530) and 100 (22–300) in SMART and FIRST, respectively. All of the biomarkers were inversely associated with baseline CD4 in FIRST but not in SMART. Curves of CD4 change over time by pre-ART biomarker quartiles significantly overlapped for all biomarkers. In adjusted models, there was no significant relationship between baseline biomarker levels and mean change in CD4 (P for trend: CRP: 0.97; IL-6: 0.25 and D-dimer: 0.29). Sensitivity analyses yielded similar results. Conclusion: Pre-ART inflammation/coagulation activation markers do not predict CD4 response to ART. These biomarkers appear to influence the risk of clinical outcomes through mechanisms other than by blunting long-term CD4 gain. Disclosure: The SMART and FIRST studies were funded by grants from US National Institutes of Health (NIH). Kirby Institute, UNSW Australia, is funded through the Australian Government Department of Health and Ageing. No other disclosures.